Analisis Ekologi: Hubungan Faktor Risiko dengan Prevalensi Stroke di Indonesia 2018 - Indah Sari (Puslitbang Sinergis Asa Professional, 2022)
Based on the results of the 2018 Riskesdas, it shows an increasing number of people with stroke in Indonesia. Compared with the results of the 2013 Riskesdas study, the prevalence of stroke patients increased from 7% per mil to 10.9% per mil. One of the factors that cause stroke is the behavior of not controlling blood pressure, lack of physical activity, consumption of salty foods, and smoking behavior. Objective: This study aims to determine the risk factors associated with the incidence of stroke in Indonesia. Methods: This research design uses an ecological analysis approach. The secondary data source used in this study comes from the data from the 2018 Riskesdas report at the provincial level (Ministry of Health, 2018). All districts were sampled in this study. In addition to the prevalence of stroke, there are 4 other variables analyzed as independent variables, namely variables not controlling blood pressure, lack of physical activity, consumption of salty foods, and smoking behavior. Data were analyzed using cross tabulation. Results: The results showed that the consumption of salty foods was not associated with the prevalence of stroke. While the risk factors that influence are the habit of not controlling blood pressure, lack of physical activity, and smoking behavior with the prevalence of stroke in East Java. Conclusion: Several risk factors that influence is the increased prevalence of stroke is closely related to the habit of not controlling blood pressure, lack of physical activity, and smoking behavior. However, there is no relationship between food consumption and the prevalence of diabetes mellitus in East Java.